Optical spectroscopy investigation of peptides issued from the AML1-ETO–E-protein complex relevant to acute myeloid leukemia. Issue 4 (2008) - Porumb Porumb, H. H.
Abstract : The expression of AML1-ETO, resulting from the t (8; 21) chromosomal translocation causes 15% of acute myeloid leukaemias. The NHR2 region of ETO, bearing the motif LxxLL, is involved in the oligomerisation of the AML1-ETO. "Peptide NHR2" is one of the objects of the present investigation. The TAFH region of ETO may recruit AML1-ETO to transcription activators, such as E-protein. "Peptide TAFH" is another object of the present investigation. TAFH interacts with E-protein through the AD1 domain of the latter, which possesses an LxxLL motif as well. "Peptide AD1" is the third object of the present investigation. By CD, ANS fluorescence and intrinsic fluorescence, we suggest an antiparallel coiled-coil encounter of two NHR2 molecules (Kd ═2.8–4 µM) as a prerequisite to tetramer formation. On the other hand, we show that the TAFH domain would probably recognize another partner bearing the LxxLL motif and, before binding to AD1 (Kd ═28 nM), the first such interaction is likely to be intramolecular, with the NHR2 domain of the AML1-ETO protein itself (Kd ═1.28 nM). Furthermore, a possible interaction of NHR2 with AD1 is also revealed (Kd ═240 nM). The biological implications of the results are discussed.